2020
DOI: 10.3389/fpls.2020.01145
|View full text |Cite
|
Sign up to set email alerts
|

Aphid-Responsive Defense Networks in Hybrid Switchgrass

Abstract: Aphid herbivory elicits plant defense-related networks that are influenced by host genetics. Plants of the upland switchgrass (Panicum virgatum) cultivar Summer can be a suitable host for greenbug aphids (Schizaphis graminum; GB), and yellow sugarcane aphids (Sipha flava, YSA), whereas the lowland cultivar Kanlow exhibited multi-species resistance that curtails aphid reproduction. However, stabilized hybrids of Summer (♀) x Kanlow (♂) (SxK) with improved agronomics can be damaged by both aphids. Here, hormone … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 110 publications
(160 reference statements)
2
29
0
Order By: Relevance
“…Similar approaches have been used by other researchers to understand plant–aphid interactions [ 55 , 56 , 57 , 58 , 59 , 60 , 61 ]. As examples, Zhang et al [ 56 ] found that GB infestation of wheat increases endogenous reactive oxygen species (ROS) production compared to the non-phytotoxic aphid Sitobion avenae , suggesting a similarity in responses observed in Summer and hybrid switchgrass infested with GB or YSA [ 29 , 30 ]. Phloem-resident mechanisms (other than callose) can also impact aphid and virus responses [ 62 ], although it is unclear if such mechanisms are resident in Kanlow plants [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Similar approaches have been used by other researchers to understand plant–aphid interactions [ 55 , 56 , 57 , 58 , 59 , 60 , 61 ]. As examples, Zhang et al [ 56 ] found that GB infestation of wheat increases endogenous reactive oxygen species (ROS) production compared to the non-phytotoxic aphid Sitobion avenae , suggesting a similarity in responses observed in Summer and hybrid switchgrass infested with GB or YSA [ 29 , 30 ]. Phloem-resident mechanisms (other than callose) can also impact aphid and virus responses [ 62 ], although it is unclear if such mechanisms are resident in Kanlow plants [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…Transcriptional and metabolic outcomes upon infestation with GB have been evaluated in Summer switchgrass plants [ 29 ], and those of GB and YSA infestation on Summer and Kanlow switchgrass hybrids [ 30 ]. In both studies, similarities and differences were observed in the defense responses to the different aphids.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…To account for this possibility, several hypotheses have been proposed, including the heterodimerization of JA-responsive TFs with other types of TFs, and the recruitment of other co-regulators that compete to bind to the TFs. To gain a more complete understanding of how JA signaling regulates its diverse metabolic and physiological outputs, it is important to identify novel JA signaling regulators or TFs [26,49].…”
Section: Discussionmentioning
confidence: 99%